Faktor-Faktor yang Memengaruhi Non Performing Financing pada Bank Umum Syariah Indonesia Periode 2010-2014 - Yulya Aryani; Lukytawati Anggraeni; Ranti Wiliasih (Department of Islamic Economics, IPB University, 2016)
The objective of this study is to determine the internal and external factors affected non-performing financing in Islamic Banks Indonesia, 2010-2014. The samples used were 11 Islamic Banks in Indonesia 2010-2014. This study used panel data with annual data obtained from the bank's 2010 to 2014 annual reports of banks. The results showed that the Capital Adequacy Ratio (CAR), Bank size, overhead cost and SBIS rate have a significant negative effect on Non Performing Financing, while the FDR, NIM, KAP and BI rate have a significant positive effect on Non-Performing Financing. Commercial Bank needs to monitor the level of Capital Adequacy Ratio (CAR), Bank size and improve the quality of operational management on overhead cost. In addition, Islamic Banks should be more sensitive to macroeconomic conditions, especially the level of BI rate and yield rate of SBIS so it can determine precisely the financing policy in order to control the level of NPF at a reasonable level.